2021
DOI: 10.4149/gpb_2021032
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of the choroid plexus in brain diseases

Abstract: The choroid plexus, located in the ventricular system of the central nervous system (CNS), obtains numerous roles critical for the proper development and operating of the CNS. The functions range from the best-known ones of the barrier and cerebrospinal fluid (CSF) producer, through participation in immune answer, 'nourishment, detoxification and reparation of the rest of the CNS. Increase number of studies point out the association between choroid plexus dysfunction, characterized by alterations in secretory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 217 publications
(273 reference statements)
0
4
0
Order By: Relevance
“…5 It is well established that the choroid plexus, located within the ventricular system of the central nervous system (CNS), plays an important role in the implementation of the immune response within the CNS. 6 The plexus is essential for the production of CSF, 7 but also responsible for regulating entry of immune cells and specific molecules to the brain parenchyma, providing a gateway for antigen trafficking between the CSF and the vascular circulation. 8,9 Several recent publications have demonstrated an association between plexus volume and the degree of inflammation in brain tissue, suggesting that plexus volume may serve as a surrogate marker for MS disease activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It is well established that the choroid plexus, located within the ventricular system of the central nervous system (CNS), plays an important role in the implementation of the immune response within the CNS. 6 The plexus is essential for the production of CSF, 7 but also responsible for regulating entry of immune cells and specific molecules to the brain parenchyma, providing a gateway for antigen trafficking between the CSF and the vascular circulation. 8,9 Several recent publications have demonstrated an association between plexus volume and the degree of inflammation in brain tissue, suggesting that plexus volume may serve as a surrogate marker for MS disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the choroid plexus, located within the ventricular system of the central nervous system (CNS), plays an important role in the implementation of the immune response within the CNS 6 . The plexus is essential for the production of CSF, 7 but also responsible for regulating entry of immune cells and specific molecules to the brain parenchyma, providing a gateway for antigen trafficking between the CSF and the vascular circulation 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4 We recently demonstrated that lesion expansion is most noticeable in close proximity to ventricles, suggesting a link between slow burning inflammation and cerebrospinal fluid (CSF). 5 It is well established that the choroid plexus, located within the ventricular system of the central nervous system (CNS), plays an important role in the implementation of the immune response within the CNS 6 . The plexus is essential for the production of cerebrospinal fluid (CSF) 7 , but also responsible for regulating entry of immune cells and specific molecules to the brain parenchyma, providing a gateway for antigen trafficking between the CSF and the vascular circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The choroid plexus (CP), located within the brain's ventricular system, plays an important role in the implementation of the immune response within the central nervous system (CNS) (Mihaljevic et al 2021). The CP is essential for the production of cerebrospinal fluid (CSF) (Hofman and Chen 2016); and critically determines brain homeostasis by regulating the entry of immune cells and specific molecules into the brain parenchyma.…”
Section: Introductionmentioning
confidence: 99%